Association between Profile of the Respondent and Impact of Integrated Farming System in Terms of Change in Employment Generation - Ruikar B. A.,; Gaikawad A. B.,; Dangore A. P.,; Kadam J. R., (Archives of Current Research International, 2024)
The present study highlights about impact of integrated farming system on doubling farmers’ income. The study was conducted in four district of Konkan regions of Maharashtra namely Ratnagiri, Sindhudurg, Raigad and Palghar district, India. For farmers with limited resources, the Integrated Farming System (IFS) is the only way to ensure a stable living and a means of subsistence. Sustainable livelihood through crop diversification, including the introduction of high-value crops, planned strategies for overcoming various obstacles, and the road of successful marketing, all made possible by integrated farming modules that are ideal for farmers to encourage scientific farming practices. The present study was conducted in four district of Konkan region of Maharashtra. A multistage sampling procedure was adopted for the selection of integrated farming system adopters. In all 200 respondents were selected for study from the four districts of Konkan region. The “Ex-Post-Facto” research design was used for the proposed study. The impact of the integrated farming system was found to be significantly correlated with thirteen selected independent variables, including age, farming experience, major occupation, annual income, cropping pattern, livestock possession, information seeking behavior, economic motivation, irrigation status, and risk orientation. Additionally, the impact of the integrated farming system was found to be highly correlated with education, land holding, and productivity level, particularly in terms of the change in employment generation.